A Comprehensive Approach to Compatibility Testing Using Chromatographic, Thermal and Spectroscopic Techniques: Evaluation of Potential for a Monolayer Fixed-Dose Combination of 6-Mercaptopurine and Folic Acid - Edvin Brusač; Mario-Livio Jeličić; Matija Cvetnić; Daniela Amidžić Klarić; Biljana Nigović; Ana Mornar (MDPI AG, 2021)
In this work, a systematical compatibility investigation of 6-mercaptopurine and folic acid, two commonly used medications in the treatment of inflammatory bowel disease, for the needs of a fixed-dose combination development strategy is shown. Various techniques and approaches, such as differential scanning calorimetry, isothermal stress testing, attenuated total reflectance-Fourier-transform infrared spectroscopy, dissolution medium stability and forced degradation studies, were used to elucidate the possible interactions from different aspects. The results predominantly point to the absence of physicochemical interactions between the examined substances in a variety of possible conditions. However, the forced degradation of the blend of substances and excipients in basic conditions showed a drastic degradation of 6-mercaptopurine, signifying that attention needs to be directed to the careful selection of the excipients for the formulation. To sum up, our findings indicate that a fixed-dose combination of 6-mercaptopurine and folic acid could be produced using one formulation blend, immensely simplifying its manufacture.